2015
DOI: 10.1161/atvbaha.115.305678
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Protein Scrib Facilitates Endothelial Inflammatory Signaling

Abstract: Objective— The polarity protein Scrib is highly expressed in endothelial cells and is required for planar cell polarity. Scrib also facilitates recycling of integrin α5 to the plasma membrane. Because integrin α5 signals the presence of the inflammatory matrix protein fibronectin, we hypothesized that Scrib contributes to endothelial inflammatory signaling. Approach and Results— Cytokine treatment of human umbilical vein endothelial cells induced an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…7 , E–G ) was equally effective as the blocking peptides in reducing the interaction signal. The overall signal intensity in the experiments focusing on endogenous NOX4 was much lower than after overexpressing ( 35 ) the protein and required more amplification. Also the signal to background ratio was lower as the antibodies used were not made for immunofluorescence and as murine cells compared with human cells yield a different unspecific reaction pattern.…”
Section: Resultsmentioning
confidence: 93%
“…7 , E–G ) was equally effective as the blocking peptides in reducing the interaction signal. The overall signal intensity in the experiments focusing on endogenous NOX4 was much lower than after overexpressing ( 35 ) the protein and required more amplification. Also the signal to background ratio was lower as the antibodies used were not made for immunofluorescence and as murine cells compared with human cells yield a different unspecific reaction pattern.…”
Section: Resultsmentioning
confidence: 93%
“…SCRIB, which is overexpressed in endothelial cells and is essential for planar cell polarity and serves as a novel proinflammatory regulator in endothelial cells ( 27 ). Altman and Kong ( 28 ) demonstrated that protein kinase C proteins (PKCs) serve essential roles in human immune disorders, and can be used as therapeutic targets in several immune disorders including autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Polarity proteins work by regulating many aspects of cellular differentiation and proliferation, including junctional protein formation and localization 101,102 . Although the understanding of polarity complexes is mainly supported by a wide range of experiments involving epithelial cells, the complexes also play pivotal roles in endothelial cells 103,104 . Thus, impairments to polarity complexes could subsequently result in damage to transmembrane and cytoplasmic junctional proteins.…”
Section: Sars-cov-2 Infection Induces a Cytokine Storm That Causes DImentioning
confidence: 99%